(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Objectives: This present study was envisaged to identify the effect of analgesic and anti-inflammatory activity forethanolic root extract of Allium cepa L. Methodology: The study was carried out using Sprague- Dawley rats (250- 300g) and Albino mice (25- 30g). Diclofenac sodium and Tramadol are the standard drugs, was prepared by dissolving in distilled water to make the concentration of 10mg/kg and 20mg/kg for anti-inflammatory and analgesic activity respectively. The effect of ethanolic extract of A.cepa L root was investigated for analgesic activity using tail immersion method. The anti-inflammatory activity of ethanolic root extract of A.cepa was studied using carrageenan-induced paw edema to the rats.Results: The anti-inflammatory activity was evaluated using carrageenan method in Sprague- Dawley rats. The anti-inflammatory activity was found to be dose dependent in carrageenan induced paw edema model. The ethanolic extract has shown highly significant (p<0.001) percentage of inhibition of paw edema, 57.43% and 60.56% at 5th hour at the low dose and high dose, respectively. Whereas analgesic activity was studied using tail immersion method in mice. The ethanolic root extract was shown highly significant (p<0.001) analgesic activity with standard drug and high dose but, low dose showed less significant (p<0.05) analgesic activity. Conclusions: The findings of the present study concluded that A.cepa L roots have potential to treat pain and inflammation and as a good source, novel natural analgesic and anti-inflammatory agents. The ethanolic extract of A.cepa L root showed highly significant analgesic and anti-inflammatory activity in mice and rats respectively.